Formulation-driven additive manufacturing of 3YSZ advanced ceramics via digital light processing - Athanasios Goulas; Basar Ozkan; Sina Saremi-Yarahmadi; Bala Vaidhyanathan (Open Ceramics)
Zirconia is a key advanced ceramic due to its high mechanical strength, thermal stability, and biocompatibility. However, vat photopolymerisation-based additive manufacturing of zirconia presents challenges requiring advanced formulations and processing. This study demonstrates the successful fabrication of 3 mol.% yttria-stabilised zirconia (3YSZ) using digital light processing (DLP). Complex green bodies were shaped from ceramic suspensions with 46 vol.% solids (82 wt.%), followed by thermal binder removal and sintering at 1475 °C for 4 h. The 3D-printed structures achieved 99.4 ± 0.2 % density and an average Vickers microhardness of 1244.2 ± 98.2 HV1/10 (12.2 ± 0.96 GPa). This work highlights that dense, robust 3YSZ components can be produced using low-cost DLP equipment, broadening accessibility in advanced ceramic additive manufacturing.